2021
DOI: 10.1016/j.jhazmat.2021.125092
|View full text |Cite
|
Sign up to set email alerts
|

Direct imaging evidences of metal inorganic contaminants traced into cigarettes

Abstract: Today, environmental health research of adverse hybrid materials diffused by cigarette represents a new challenge for identifying new health risks directly related to the specific micro-sized materials in terms of their morpho-chemical features. Distinctive assumptions about the origin, the evolution? growth, and the functionalization of toxic elusive particles have been proposed by scientific research to attend the relevant toxicological aspects of observable behaviors. Therefore, direct morpho-chemical obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…The surface collapse was prevented by carefully regulating the chamber pressure and cooling temperature. To avoid radiation damage and drifting images, all samples were examined at an accelerating voltage based on the pressure/temperature parameters, as reported elsewhere in our previous studies [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…The surface collapse was prevented by carefully regulating the chamber pressure and cooling temperature. To avoid radiation damage and drifting images, all samples were examined at an accelerating voltage based on the pressure/temperature parameters, as reported elsewhere in our previous studies [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…With respect to the articles identified that described chemical analyses of HTPs, articles or portions of their results were excluded from detailed discussion in this section of the review if they did not detail a direct quantitative comparison between the HTP(s) under investigation and other nicotine-or tobacco-containing products such as cigarettes and/or EVPs (i.e., quantitative data were reported solely for the HTP(s) investigated) [20][21][22][23][24]; only provided an analysis of chemical constituents present in consumables or only provided an analysis of emissions released by consumables using an experimental methodology which did not involve use of the consumable combined with the operation of the associated handheld device as intended by the manufacturer (i.e. creating an exposure scenario different from that of real-world product use) [25][26][27][28][29][30][31][32]; only provided an analysis of nicotine levels present in HTP aerosol and mainstream cigarette smoke without further detail [33].…”
Section: Aerosol Chemistrymentioning
confidence: 99%
“…Nađene su mikročestice visoko toksičnih metala sastavljene od vanadija, kroma, željeza, nikla, bakra te urana. 24 Za razliku od e-tekućina, filtri HNBT uređaja pokazuju visoku ekotoksičnost i moguće je da će postati velik ekološki problem u budućnosti. 22 4.…”
Section: Uređaji Za Zagrijavanje Duhanaunclassified